Combined effect of sulphur and boron on yield and yield contributing characters, nutrient and oil content of mustard (Bangladesh Journal of Agricultural Research, 2017)
This experiment was conducted in the experimental field of Sher-e-Bangla Agricultural University, Dhaka during 2014-2015 to know the combined effect of different levels of sulphur (S) and boron (B) on yield and yield contributing characters, nutrient and oil content of mustard and to find out the suitable combination of sulphur (S) and boron (B) for yield maximization of mustard. There were 16 treatment combinations comprising four levels each of S (S0= 0, S1=10, S2= 20 and S3= 30 kg S ha-1) and B (B0= 0, B1= 1, B2= 2 and B3= 3 kg B ha-1). It was replicated thrice in a randomized complete block design. Results showed that the combination of S and B (20 kg S ha-1 and 3 kg B ha-1) contributed positively for better performance of yield contributing characters of mustard. The combination S2B3 (20 kg S ha-1 and 3 kg B ha-1) produced the highest grain yield (2180 kg ha-1) followed by S3B2 and S3B3 treatment combination. The highest protein and oil content of mustard were recorded from S3B3 (30 kg S ha-1 and 3 kg B ha-1) treatment followed by S2B3 treatment combination. Therefore, the combination of S and B (20 kg S ha-1 and 3 kg B ha-1) might be suitable dose for cultivation of mustard in tejgaon series soils under agro-ecological zone of 28 (Madhupur Tract) Bangladesh.Bangladesh J. Agril. Res. 42(2): 249-258, June 2017